Glass transition temperature of asphalt binder based on atomistic scale simulation - Fang, Yongwei; Pang, Yingying; Zhang, Jiandong; Nie, Yihan; Lu, Hongquan (Frontiers in Materials, 2024)
Glass transition is one of the most crucial physical properties for polymerical materials. As a typical complex polymerical material, the glass transition phenomenon in asphalt binder is directly related to their temperature-related properties. To investigate the glass transition characteristics, this study delves into the glass transition temperature of asphalt binder based on molecular dynamics simulations. It is found that the calculation range for the glass transition temperature sits between 100 and 400 K. The evolution of asphalt binder structure is influenced by different cooling rates, where lower cooling rates allow sufficient microstructural rearrangement, resulting in a smaller volume at the lower temperature. Model size is closely associated with the glass transition region. As the size increases, the transition region significantly expands. Increasing the model size also reduces volume fluctuations after isothermal relaxation, providing more stable volume changes. It is observed that higher cooling rates with a model size over 100 Å can well reproduce the glass transition process of asphalt binders. This work provides atomic-scale insights for the glass transition phenomenon in asphalt binder, which could be beneficial for the design of high-performance asphalt binder.